The study of effect of Treatment, Study habits and their interaction on Tolerance of Ambiguity by taking pre-test scores of Tolerance of Ambiguity as covariate on Commerce students of Class XI (Journal of Advances and Scholarly Researches in Allied Education, 2023)
With the fast advancement of technology in the final part of the 20th century, the scientificmanagement side of company received increasing attention. Government enacted a number oflegislation, which led to a perceived demand for experts in the subject. As a result, there is a need forprofessionalized business education. Due to the following factors, business education is now utterlydisconnected from the reality of the industrial world. Lack of current teaching techniques, the use ofteaching aids, inadequate training for lecturers, and the employment of various teaching approaches.The following improvements are recommended in order to address the aforementioned issues and helpcreate in commerce students analytical tools that may be used and used in the changing business andindustrial environment. It is necessary to examine educational standards, curricula, and othercomponents on a regular basis and to consider innovative teaching approaches and teacher preparationprograms. The improvement of commerce education depends not only on the right curriculum and thecaliber of the students, but also on the teaching staff and methodologies.